Digitalization As a Socio-Economic Challenge: Modeling the Impact On the Level of Cybercrime Considering Socio-Economic, Technological and Institutional Factors - Hanna Yarovenko; Olha Horbachova; Roman Bylbas; Dmytro Latysh (SocioEconomic Challenges, 2025)
Today, digital technologies are not just changing reality – they are closely intertwined, forming a new ecosystem. This process brings numerous benefits: fast decision-making, automation of routine tasks, and access to information in one click. At the same time, along with new opportunities, new socio-economic challenges arise – cybercrime is rapidly evolving, acquiring complex forms, prevalence and danger. Hacker attacks, data leaks, and digital fraud have become real challenges that affect not only individual users, but also businesses, state institutions and national security. The digital world has given humanity incredible freedom, but at the same time, new forms of vulnerability. The study is devoted to modelling (based on correlation analysis and OLS, Fixed Effects, Random Effects regression models) the impact of digitalisation on the level of cybercrime, taking into account socio-economic, technological and institutional factors based on panel data of 20 countries for the period 2015-2024. All stages of data processing, model building and visualization of results were implemented using the Python programming language. The information base is data from international organizations (ITU, World Bank, World Integrated Trade Solution), national cybersecurity reports. The analysis showed that the presence of digital infrastructure is not a decisive factor in shaping the level of cybercrime. The scale of cyber incidents is closely related to several additional factors of decisive importance. These include: state regulation of cybersecurity, national legislation, digital competence of users and the technological potential of cybercriminals. The analysis by country confirms that the scale and nature of the impact of digital technologies on the level of cybercrime are largely shaped by institutional maturity, the presence of effective cyber policies, social responsibility of users and the ability of the state to respond promptly to digital challenges. The differences identified between countries with a similar level of digital development, but different levels of security, serve as additional evidence that digitalization is only a condition, not a cause, of the increase in cyber incidents. The results can be used to shape digital policy, improve cybersecurity strategies and predict cyber risks in countries with transformational economies.